The Cognitive and Behavioural Profile of Amyotrophic Lateral Sclerosis: Application of the Consensus Criteria - Monica Consonni; Sandro Iannaccone; Chiara Cerami; Paola Frasson; Marco Lacerenza; Christian Lunetta; Massimo Corbo; Stefano F. Cappa (Behavioural Neurology)
Objective: The study aims to assess the spectrum of cognitive and behavioural disorders in patients affected by Amyotrophic Lateral Sclerosis (ALS) according to the recent consensus criteria [9]. The study also intends to assess the impact of physical disability on cognitive and behavioural abnormalities.